The Relationship between Leadership Styles and Job Satisfaction in the Malaysian Textile Industry - Hee, Ong Choon; Ying, Ng Xin; Kowang, Tan Owee; Fei, Goh Chin; Yew, Lim Kim; Teck, Tan Seng; Hoo, Wong Chee (International Journal of Psychosocial Rehabilitation, 2020)
In Malaysia, textile industry is facing several issues such as decline in performance, shortage of new talents and challenges to retain existing employees. The purpose of this study is to investigate the relationship between leadership styles and employee job satisfaction in the textile industry in Malaysia. The leadership styles investigated in this study are transformational leadership, transactional leadership and laissez- faire leadership. In addition, the level of employee job satisfaction in this industry has also been analyzed. This research proposed a conceptual framework that links the leadership styles with employee job satisfaction. In this study, survey questionnaire was used to collect data from the target respondents and a total of 140 responses was obtained from the survey. Although the findings show that all the leadership styles were significantly associated with job satisfaction, the dominated leadership styles were transformational and transactional leadership. Employees were found moderately satisfied with their job. The research findings are useful for the top management to determine appropriate leadership style to adopt in order to improve their employee job satisfaction level.